Aplikasi E-Learning Berbasis Progressive Web App Pada Apologetika Indonesia - James Riady; Henry Novianus Palit; Justin Andjarwirawan (Jurnal Infra, 2019)
Apologetika Indonesia  are religious organizations that support the defense of Christian faith that supports the truth related to Christianity. The method used in the discussion of apologetic content is by holding seminars and lectures in churches throughout Indonesia. Supposedly, with the existing technology, the spread of content can be done easily through the internet, namely through the apps. The media used must also be resilient to bad internet conditions because the spread of content wants to reach places that might have poor internet conditions. But the Apologetika Indoesia also does not have a website to run the online course.The author makes a website and conducts research on performance measurement between standard websites and websites that have a Progressive Web App. The results show that websites with progressive web applications have a worse performance than ordinary sites. However, in testing Progressive Web App , websites that use Progressive Web App can respond better, especially at points that can respond offline. In situations of poor internet connection, it cannot be denied that websites that use Progressive Web Applications can respond much better than ordinary websites.